COMMUNICATIONS IN THE ORGANIZATIONAL DECISION MAKING TO OVERCOME THE CONFLICT - Fifi Hasmawati Hasmawati (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2017)
This study aims to explore the extent to which communication can resolve conflicts within the organization. Conflict within the organization can occur at any time, either in the form of conflict between individuals as members of the organization, as well as conflicts between members and organizations. Conflict is certainly very unfavorable for leadership because it will cause difficulties in moving members to work together, in an effort to achieve common goals. In this condition the participation of members not only decreases, but also eludes and challenges as a sign of less or ineffective leadership. Conflict encourages individuals to seek friends to show their self-solidarity and problems, resulting in grouping of members opposed to others, either explicitly or clandestinely. Key Words; Communication, Organizational decision making, Conflict